Genetic Variant of C-5434T REN Enhancer on Serum Renin Levels and Binding Pattern of Signal Transducers and Activators Transcription 3 - Imama Maslahah; Mohammad Saifur Rohman; Nashi Widodo; Agustina Tri Endharti; Didik Utomo (International Journal of Hypertension)
The human renin gene has been widely known to be involved in essential hypertension (EH) pathogenesis. Genetic variant C-5434T of REN enhancer contributed to renin gene transcription and serum renin regulation. However, the mechanism associated with the transcription level changes remains unknown, and only a few reports exist that discussed serum renin levels on C-5434T of REN. Thus, this study aims to investigate the relationship between genetic variant C-5434T of REN enhancer and serum renin levels in Indonesian hypertensive patients. SNP of C-5434T was genotyped in 56 hypertensive patients by using RFLP. The data showed that serum renin is slightly higher in hypertensive patients with the TT genotype (39 ± 10.3) than patients with the CC genotype (33 ± 10.6) but the difference was not statistically significant (p=0.35). Here, we also present a docking approach for predicting interaction between genetic variant -5434C/T and STAT3 (Signal Transducers and Activators Transcription 3), the predicted transcription factor that regulates renin gene enhancer. The results showed that STAT3-DNA allele T more favorably binds to DNA than STAT3-DNA allele C. These data suggest that the presence of genetic variant C-5434T has changed the binding pattern of STAT3 to REN enhancer. This is likely to influence STAT3 activity to stimulate the expression of renin gene in producing renin.